TECHNOLOGY FOR UTILIZING BY-PRODUCTS OF PROCESSED STRIPED CATFISH (Pangasianodon hypophthalmus) AS FOOD RAW MATERIALS - Diana, Ayu; Syahrul, Syahrul; Fikri, M. Zakiyul (Asian Journal of Aquatic Sciences, 2024)
Striped catfish (Pangasianodon hypopthalmus) is well known in Asia, specifically in Southeast Asia, such as Vietnam, Thailand, Indonesia, Malaysia, Cambodia, Burma, and Brunei Darussalam. Currently, catfish have been exported to almost all countries in the world. This study aims to analyze the chemical composition of processed catfish by-products and find alternatives for their economic utilization. The research method used is the experimental method, namely conducting experiments on using processed by-products of catfish as food raw materials. Furthermore, quality analysis was performed on processed by-products and raw food materials, namely proximate analysis and amino acid profile. Proximate analysis of processed catfish by-products (meat attached to bones, belly fat, fish bones, and offal) includes protein, fat, water content, carbohydrates, and amino acids. These by-products are still classified as functional. Therefore, this research utilizes these by-products in food raw materials. The chemical analysis (proximate) results of the products produced showed numbers that meet SNI quality standards as food products. By-products of catfish processing (fillets and smoked catfish) can be utilized as food raw materials in the form of fish concentrate flour, fish bone meal, and fish oil.